Analysis of business/management communication course curriculum in top universities in Asia, Australia and New Zealand. - Lye, Sook Wan. (2008)
The main purpose of this study was to examine the variations in the design of Business/Management Communication courses offered at undergraduate and graduate levels in Asia, Australia and New Zealand. Data on the Business/Management Communication courses were collected from various universities in Asia, Australia and New Zealand. The general course profile, perceptions of other business faculty of the Business/Management Communication course, and the availability of additional tuition facilities are presented and discussed.